2018
DOI: 10.1038/s41467-018-04204-w
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiomes of wild great apes fluctuate seasonally in response to diet

Abstract: The microbiome is essential for extraction of energy and nutrition from plant-based diets and may have facilitated primate adaptation to new dietary niches in response to rapid environmental shifts. Here we use 16S rRNA sequencing to characterize the microbiota of wild western lowland gorillas and sympatric central chimpanzees and demonstrate compositional divergence between the microbiotas of gorillas, chimpanzees, Old World monkeys, and modern humans. We show that gorilla and chimpanzee microbiomes fluctuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
229
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(255 citation statements)
references
References 77 publications
25
229
1
Order By: Relevance
“…To investigate the extent to which the composition of the gut microbiome overlaps across different primates for both known and currently uncharacterized microbes, we meta-analyzed a large set of gut microbiomes from humans and non-human primates (NHPs) that are publically available. Six datasets were considered for NHPs [30,[37][38][39][40][41] spanning 22 host species from 14 different countries in 5 continents (Additional file 1: Table S1 and Additional file 2: Figure S1), totaling 203 metagenomic samples that we retrieved and curated for this work. Microbiome samples from adult human healthy individuals were retrieved from 47 datasets considered in a recent meta-analysis [11] on 9428 human gut metagenomes and used as a comparative resource.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate the extent to which the composition of the gut microbiome overlaps across different primates for both known and currently uncharacterized microbes, we meta-analyzed a large set of gut microbiomes from humans and non-human primates (NHPs) that are publically available. Six datasets were considered for NHPs [30,[37][38][39][40][41] spanning 22 host species from 14 different countries in 5 continents (Additional file 1: Table S1 and Additional file 2: Figure S1), totaling 203 metagenomic samples that we retrieved and curated for this work. Microbiome samples from adult human healthy individuals were retrieved from 47 datasets considered in a recent meta-analysis [11] on 9428 human gut metagenomes and used as a comparative resource.…”
Section: Resultsmentioning
confidence: 99%
“…1a and Additional file 1: Table S1) to test the influence of folivory on its composition and function and highlighted that host phylogeny has a stronger influence than diet. With a similar approach, [30] shotgun sequenced 19 wild western lowland gorillas (Gorilla gorilla gorilla) in the Republic of the Congo as part of a 16S rRNA study including sympatric chimpanzees and modern human microbiomes that demonstrated the compositional divergence between the primate clades' microbiome and the seasonal shift in response to changing dietary habits throughout the year. Orkin et al [40] exposed similar seasonal patterns linked with water and food availability by surveying the microbiome of 20 wild white-faced capuchin monkeys (Cebus capucinus imitator) in Costa Rica.…”
Section: Analyzed Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Chevalier et al, ; David et al, ; Ferguson et al, ; Jehrke, Stewart, Droste, & Beller, ; Obadia, Keebaugh, Yamada, Ludington, & Ja, ; Ramsby, Hoogenboom, Whalan, & Webster, ), which may differ systematically between laboratory and field conditions. Where studied, considerable variation in the gut microbiota composition has been demonstrated in natural animal populations (Adair, Wilson, Bost, & Douglas, ; Hicks et al, ; Jones et al, ; Martinson, Douglas, & Jaenike, ; Webster, Consuegra, Hitchings, & Leaniz, ), but whether and how this variation relates to functional traits of the animal host is largely unknown.…”
Section: Introductionmentioning
confidence: 99%